Changes in Serum Natriuretic Peptide Levels after Percutaneous Closure of Small to Moderate Ventricular Septal Defects. (26th April 2012) - Kaya, Yuksel; Akdemir, Ramazan; Gunduz, Huseyin; Murat, Sani; Bulut, Orhan; Kocayigit, İbrahim and Vatan, M. Bulent and Cakar, M. Akif and Yeter, Ekrem and Kilic, Harun and Agac, Mustafa Tarik and Acar, Zeydin
Abstract : Background . B-type natriuretic peptide has been shown to be a very sensitive and specific marker of heart failure. In this study, we aimed to investigate the effect of percutaneous closure of ventricular septal defects with Amplatzer septal occluders on brain natriuretic peptide levels. Methods . Between 2008 and 2011, 23 patients underwent successfully percutaneous ventricular septal defect closure in 4 cardiology centers. Brain natriuretic peptide levels were measured in nine patients (4 male, mean ages were 25.3 ± 14.3 ) who underwent percutaneous closure with Amplatzer occluders for membranous or muscular ventricular septal defects were enrolled in the study. Brain natriuretic peptide levels were measured one day before and one month after the closure. Patients were evaluated clinically and by echocardiography one month after the procedure. Results . Percutaneous closures of ventricular septal defects were successfully performed in all patients. There was not any significant adverse event in patients group during followup. Decrease in brain natriuretic peptide levels after closure were statistically significant (97.3 ± 78.6 versus 26.8 ± 15.6, P = 0.013 ). Conclusion . Brain Natriuretic Peptide levels are elevated in patients with ventricular septal defects as compared to controls. Percutaneous closure of Ventricular Septal Defect with Amplatzer occluders decreases the BNP levels.